Sistem Manajemen Arsip Elektronik Terintegrasi (ARTERI) Di Perpustakaan Dan Kearsipan Kabupaten Labuhanbatu Berbasis Web - Siregar, Peni Ungkasara; Nasution, Marnis (Universitas Labuhanbatu, 2022)
Electronic filing systems have not been widely used by organizations or companies. Most organizations or companies still apply conventional archive systems in managing their records. Not even a few organizations or companies that do not have a system for managing records, both conventional and electronic archive systems. The number of jobs related to archives and documents faced with conventional archive management is the beginning of the emergence of a bright spot towards creating a system that is able to reduce the workload of archiving officers or archivists in managing archives. The system is a conventional filing system that is applied in the form of software using electronic media based on the use of computers or can be said to be an electronic filing system. The preparation and manufacture of the system was carried out by the Archives Subdivision of the Labuhanbatu Library and Archives Service. In contrast to archive management which is managed conventionally, the archive system is managed in the form of archives electronically. ARTERI is a web-based electronic archive management application. Aims to facilitate archive management and to be able to integrate archives electronically.